SEKSISME DALAM KESANTUNAN BAHASA KOMPLAIN - Indah Arvianti (Master Program in Linguistics, Diponegoro University, 2011)
In interaction, people do a cooperative relationship among them. If they intend to ask something, they can express the idea in strategies in order to gain the goal. One strategy to fulfill the intention is politeness. By doing politeness speaker tends to avoid the ‘face’ of hearer, such as insulting or directing. Politeness influenced by power, social distance, and weight of imposition can be expressed by positif and negative politeness to lessen the irritating of the hearer. Complaining letter in readers’ forum is a means for readers to complain their problem in newspapaper. The question arises: Do the readers apply politeness in complaining in order to avoid FTA? This paper tries to answer the question by giving some examples of analysis of politeness strategy. Besides, the difference strategy of male and female will also be discussed. Those strategies affect the difference patern of readers forum written by male or female showing the sexism